The Influence of Relationship Marketing on Debtor Loyalty Mediated By Relationship Quality, Empirical Study at Bank Sumatra Southern Section - Silke Sachanovrissa (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
One of the strategies implemented by the banking sector is to apply the concept of relationship marketing (RM). Relationship marketing (RM) is very helpful for companies in fostering good relationships with customers, debtors, and shareholders. In this study, the direction of the research was to examine how important the quality of the relationship between regional bank customers (Bengkulu Bank, Jambi Bank and Bank Lampung) had a positive impact in increasing the relationship marketing / RM dimensions (customer trust, customer commitment, and communication) to loyalty. This study uses an explanatory survey approach with a quantitative analysis approach. The population in this study were debtor customers at three regional-owned banks, namely Bengkulu Bank, Jambi Bank and Lampung Bank. The number of research samples were 520 respondents. The sampling method used a purposive sampling approach. The analytical tool used is Structural Equation Modeling (SEM) using the LISREL 8.7 program.